2022
DOI: 10.1038/s41467-022-32452-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression plasticity regulates intraspecific variation in the acclimatization potential of a reef-building coral

Abstract: Phenotypic plasticity is an important ecological and evolutionary response for organisms experiencing environmental change, but the ubiquity of this capacity within coral species and across symbiont communities is unknown. We exposed ten genotypes of the reef-building coral Montipora capitata with divergent symbiont communities to four thermal pre-exposure profiles and quantified gene expression before stress testing 4 months later. Here we show two pre-exposure profiles significantly enhance thermal tolerance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 88 publications
4
26
0
Order By: Relevance
“…Our ndings are consistent with recent reports that show that coral communities can acclimatize to increasing levels of thermal stress (17,23), which can be explained by the potential ability of corals to enhance their thermal tolerance through multiple mechanisms (30,31). For example, shifts in gene expression enable corals to acclimate to thermal stress (22,32). Such acclimatization processes can be anticipated at community scales and may vary among reef zones (33) or even regions such as the reefs of the eastern tropical Paci c, which have shown to be highly resilient after encountering acute thermal stress (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our ndings are consistent with recent reports that show that coral communities can acclimatize to increasing levels of thermal stress (17,23), which can be explained by the potential ability of corals to enhance their thermal tolerance through multiple mechanisms (30,31). For example, shifts in gene expression enable corals to acclimate to thermal stress (22,32). Such acclimatization processes can be anticipated at community scales and may vary among reef zones (33) or even regions such as the reefs of the eastern tropical Paci c, which have shown to be highly resilient after encountering acute thermal stress (34).…”
Section: Discussionsupporting
confidence: 92%
“…However, the cumulative stress of past disturbances is also a key determinant of the responses of organisms and ecological communities to stress. This is known as the ecological memory of previous events, and can be generated by various biological mechanisms, including acclimatization, adaptation, or even shifts in species composition (5,22). In the Great Barrier Reef, it has been recently shown that the severity of coral bleaching depends on the heat exposure of previous bleaching events (17).…”
Section: Introductionmentioning
confidence: 99%
“…Like most organisms, corals have the ability to acclimatize to environmental change, which reduces the severity of bleaching and mortality during thermal stress (Middlebrook et al, 2008;Bellantuono et al, 2012;Palumbi et al, 2014;Bay and Palumbi, 2015;Foo and Byrne, 2016;Schoepf et al, 2019;Majerova et al, 2021). However, this natural phenomenon is genotype-specific (Dilworth et al, 2021;Drury et al, 2022) and could be lost under future climate-change scenarios (Ainsworth et al, 2016). One of the main obstacles to the application of this strategy for conservation (van Oppen et al, 2015 Transcriptomic data from acclimatized corals shed light on the main gene families and cellular pathways that play a role in the bleaching process, but functional studies have been largely missing in reef-building corals (Bellantuono et al, 2012;Palumbi et al, 2014;Bay and Palumbi, 2015;Thomas et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As sedentary animals, they have only a limited ability to avoid stressful environmental conditions, thus their potential to react to dynamic changes in their surrounding is crucial for their survival. An increasing body of knowledge demonstrates various mechanisms (gene expression or morphological plasticity, i.e (Kenkel and Matz, 2017;Drury et al, 2022;Brambilla et al, 2022).) that corals employ to promote resilience.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the influences of thermal stress on coral growth plasticity, bleaching tolerance, and skeletal properties may be related to zooxanthellae communities, microbiome composition, and coral gene expression patterns [20][21][22]. Hermatypic coral adapt to the rising temperature through positive regulation of innate immune responses, protein ubiquitination and apoptosis [23]. At present, it is universally admitted that transcriptome sequencing technology is beneficial for enlightening and evaluating how ecological factors affect scleractinian corals.…”
Section: Introductionmentioning
confidence: 99%